Iran and World Contemporary Developments (American Journal of Islam and Society, 2009)
This conference (www.iranoworld.ir), the first one to be organized by thefaculty of the Department of Political Science at Imam Khomeini InternationalUniversity (IKIU) and will be held continuously in the followingyears, sought to develop knowledge and making the ground suitable for discussingand analyzing the work of researchers both inside and outside Iran.Despite the antiquity of Iran’s history, rich oil and gas resources, andmonitoring of the strategic Persian Gulf, the country has enjoyed stability inits blend of religion and politics of social affairs in the face of profoundchange. Contemporary international relations, known for its dominatingprinciples of equal sovereignty and self-determination, is also undergoingchange, the most obvious ones being the Soviet collapse, the “new worldorder,” and globalization, all of which have affected Iran ...